Susceptibilidade de micro-organismos patogênicos frente às micocinas de Wickerhamomyces anomalus ambientais - Paris, Ana Paula (2015)
The significant increase in the incidence and prevalence of pathogenic microorganism resistance to antimicrobials has become a major public health problem, making it important to search for new therapeutic compounds against this threat. Micocyns produced by some yeasts, like Wickerhamomyces anomalus, have activity against other microorganisms, action which possibly occurs after the binding of micocyn to specific receptors on cell wall and plasma membrane of sensitive microorganisms and thus, presenting a promising antimicrobial activity. The aim of this study was to evaluate the antimicrobial action of micocyns present in the culture supernatant and in the strain cell walls of W. anomalus (WA40, WA45 and WA92) opposite the yeast and bacteria. The three strains of W. anomalus were isolated from the soil. The micocyns of W. anomalus WA40, WA45 and WA92 were tested against the bacteria Escherichia coli, Acinetobacter baumanii and Staphylococcus aureus and the yeast Candida albicans, Candida glabrata, Candida guilliermondii, Candida tropicalis and Cryptococcus neoformans. The mycocins of the three strains of W. anomalus showed inhibitory effect on the tested microorganisms and micocinas showed a little toxicity in haemolysis test on human erythrocytes. The micocyns of W. anomalus WA40, WA45 and WA92 presented a broad spectrum of action which may be promising in the development of antimicrobial drugs.